All Days 2004
DOI: 10.4043/16749-ms
|View full text |Cite
|
Sign up to set email alerts
|

Observations and Numerical Modeling of Debris Flows in the Na Kika Basin, Gulf of Mexico

Abstract: The Na Kika Basin in the eastern Gulf of Mexico experienced debris-flow events in geologically recent times (Late Pleistocene to Recent). To assess the potential risk of such debris-flows to the pipelines and structures associated with the Na Kika field development we performed a semi-quantitative risk assessment of the potential impact of debris-flows to the proposed pipeline network. The numerical model BING was used in conjunction with available sediment core information, seismic, and bathymetric data to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Log responses of the shallowest MTC in offshore Trinidad (MTC_1) show an increase in resistivity, compressional velocity, density and porosity (Shipp et al , 2004). Geotechnical measurements also indicate an increase in shear strength, with a corresponding decrease in void ratio and water content (Pirmez et al , 2004; Shipp et al , 2004).…”
Section: Seismic and Lithological Characteristics Of Mtcsmentioning
confidence: 99%
“…Log responses of the shallowest MTC in offshore Trinidad (MTC_1) show an increase in resistivity, compressional velocity, density and porosity (Shipp et al , 2004). Geotechnical measurements also indicate an increase in shear strength, with a corresponding decrease in void ratio and water content (Pirmez et al , 2004; Shipp et al , 2004).…”
Section: Seismic and Lithological Characteristics Of Mtcsmentioning
confidence: 99%
“…The Amazon Fan drillsites are in the mid to downdip position, where the stratigraphy is disrupted and appears chaotic on seismic records. In contrast, the Na Kika boring (MC-12) penetrates the flow apron that is located at the downdip terminus of the MTC and appears massive (transparent) on seismic records (Pirmez et al, 2004;Figure 3d). In contrast, the Na Kika boring (MC-12) penetrates the flow apron that is located at the downdip terminus of the MTC and appears massive (transparent) on seismic records (Pirmez et al, 2004;Figure 3d).…”
Section: Summary Of Physical Characteristicsmentioning
confidence: 99%
“…In some settings, up to 70% of the entire slope and deepwater stratigraphic column is composed of MTCs and associated deposits (Maslin et al, 2004;Newton et al, 2004). The prevalence of mass failures represents a significant threat to the security of continental slope and deep-marine engineered installations (Hoffman et al, 2004;Pirmez et al, 2004;Shipp et al, 2004). Such dangers can have a significant impact on the financial aspects of hydrocarbon exploration and development in deep-water locations.…”
mentioning
confidence: 99%
“…Shipp et al (2004), using analyses from cores, logs, and geotechnical parameters in the Amazon Fan in Brazil (Piper et al, 1997b), the Na Kika Basin debris flows in the Gulf of Mexico, and in shallow mass-transport deposits in offshore Trinidad (East Prospect, Block 25A), concluded that several physical characteristics seem to be common in these kinds of MTCs. The lithology is generally made up of muddy sediments, although in some cases, sands can be also present; log responses tend to show an increase in resistivity, compressional velocity, density, and porosity; and geotechnical measurements indicate an increase in shear strength, with a corresponding decrease in void ratio and water content (Pirmez et al, 2004;Shipp et al, 2004). All these characteristics suggest that MTCs may be considerably more consolidated shortly after deposition than other deepwater deposits, such as LCCs or hemipelagic drapes.…”
mentioning
confidence: 99%